Value-Driven Attentional Capture is Modulated by Spatial Context - Anderson, Brian A. (Vis cogn, 2014)
When stimuli are associated with reward outcome, their visual features acquire high attentional priority such that stimuli possessing those features involuntarily capture attention. Whether a particular feature is predictive of reward, however, will vary with a number of contextual factors. One such factor is spatial location: for example, red berries are likely to be found in low-lying bushes, whereas yellow bananas are likely to be found on treetops. In the present study, I explore whether the attentional priority afforded to reward-associated features is modulated by such location-based contingencies. The results demonstrate that when a stimulus feature is associated with a reward outcome in one spatial location but not another, attentional capture by that feature is selective to when it appears in the rewarded location. This finding provides insight into how reward learning effectively modulates attention in an environment with complex stimulus–reward contingencies, thereby supporting efficient foraging.